Criminal Argot (Šatrovački) and Romani Loanwords - Kubiček, Andrej (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
Starting from the assumption that the lexicon of one language - standard or some other form of it – testifies to the basic social processes, the article explores the origin and development of the so-called “šatrovački” speech. To achieve this goal, it is necessary to introduce first a conceptual difference between related phenomena: jargon, slang, and argot (šatrovački, cant, or cryptolect). Although these language varieties are often considered spontaneous and ephemeral, the paper will show that they are often permanent linguistic phenomena that characterize criminal and marginalized subcultures. A special focus will be on the emergence of new vocabulary through borrowings from the Romani language. The article explores the genesis and function of these speech practices, highlighting the similarities that exist in several European languages and that testify to similar social processes. Finally, the paper also aims to point out the porosity of symbolic boundaries between marginalized and established ways of expression through their interpenetration.